Pendidikan Melalui Permainan: Membangun Kreativitas dan Inovasi pada Generasi Digital - Indah Meilita Meilita; Masduki Asbari; Lelono Surya Timur (AGUSPATI RESEARCH INSTITUTA, 2023)
freedom to explore, collaborate and create solutions. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to an oral narrative from the Bukalapak YouTube channel entitled